Upadacitinib and filgotinib: the role of JAK1 selective inhibition in the treatment of rheumatoid arthritis - Martina Biggioggero; Andrea Becciolini; Chiara Crotti; Elena Agape; Ennio Giulio Favalli (BioExcel Publishing Ltd, 2019)
Rheumatoid arthritis (RA) is a chronic autoimmune inflammatory disease characterized by joint involvement, extra-articular manifestations, comorbidities, and increased mortality. In the last few decades, the management of RA has been dramatically improved by the introduction of a treat-to-target approach aiming to prevent joint damage progression. Moreover, the increasing knowledge about disease pathogenesis allowed the development of a new drug class of biologic agents targeted on immune cells and proinflammatory cytokines involved in RA network. Despite the introduction of several targeted drugs, a significant proportion of RA patients still fail to achieve the clinical target; so, more recently the focus of research has been shifted toward the inhibition of kinases involved in the transduction of the inflammatory signal into immune cells. In particular, two Janus kinase (JAK) inhibitors, baricitinib and tofacitinib, have been licensed for the treatment of RA as a consequence of a very favorable profile observed in randomized controlled trials (RCTs) conducted across different RA subpopulations. Both these new compounds are active on the majority of four JAK family members (JAK1, JAK2, JAK3, and TYK2), whereas the most recent emerging approach is directed toward the development of JAK1 selective inhibitors (upadacitinib and filgotinib) with the aim to improve the safety profile by minimizing the effects on JAK3 and, especially, JAK2. In this narrative review, we discuss the rationale for JAK inhibition in RA, with a special focus on the role of JAK1 selective blockade and a detailed description of available data from the results of clinical trials on upadacitinib and filgotinib.